Determination of pig immunity status after porcine reproductive and respiratory syndrome (PRRS) modified live virus (MLV) vaccination with ELISA and PCR technique - Chua, Vi Vian (2016)
Porcine reproductive and respiratory syndrome (PRRS) is a disease characterised by late-term reproductive failure in sows and gilts, and respiratory problems in piglets and growing pigs. In this study, 240 sera were collected from four farms that had been practicing different PRRS vaccination regime for more a year and vaccinations were done at 2 months before sampling. 15 sera from four age groups: sows, growers, weaners and piglets were collected from each farm and analysed using IDEXX PRRS X3 ELISA for PRRSV antibodies. Pooled serum samples were tested by using nested-PCR that enable the differentiation of Type I and Type II PRRSV. Out of 80 pooled serum samples, none were positive for PRRSV indicating all age groups were not viraemic after vaccination. As for ELISA, results showed all the farms were seropositive for PRRS. Mean S/P ratios of piglets, growers and sows of all four farms were higher than 0.4 which was the cut off value of positive ELISA result but there were no significant difference between the farms except for Farm B which practiced whole herd US MLV vaccination. Farm B showed significantly lower (p<0.05) S/P ratio in their piglet, grower and sow groups which suggest there was low virus circulation in herd. Farm A which practiced US MLV on sow was the only farm found to have seronegative status in their weaners. Thus, these data indicate PRRS MLV vaccination will not cause viraemia and whole herd MLV vaccination may help to reduce virus circulation in PRRS endemic farm.